Development of electrode and electrolyte materials for solid-state batteries based on Li1.3Al0.3Ti1.7(PO4)3 - I Lisovskyi; V Barsukov; S Solopan; A Belous; V Khomenko; N Stryzhakova; Y Maletin (Nano Express)
The dependence of the electrochemical characteristics of a layered cathode material containing LiNi _0.5 Mn _0.3 Co _0.2 O _2 on the method for applying a protective layer of nanoparticles of the lithium-conducting material Li _1.3 Al _0.3 Ti _1.7 (PO4) _3 with a NASICON structure to its surface has been studied. The surface modification has been found to improve the capacity retention in prolonged charge/discharge cycling (up to 15%) and to allow fast charge/discharge processes. The possibility of using a composite electrolyte consisting of a porous ceramic matrix of aluminum-substituted lithium titanium phosphate Li _1.3 Al _0.3 Ti _1.7 (PO4) _3 with a transition layer of liquid electrolyte LP-71 has been shown. The use of a thick composite solid electrolyte results in a slight reduction (∼5–7 mAh g ^−1 ) in initial capacity compared to laboratory cells with the widely used Celgard 2400 separator impregnated with liquid electrolyte. Laboratory cells assembled with a composite electrolyte showed higher stability during charge/discharge cycling: after 80 deep charge/discharge cycles, the capacity reduction was ∼12% for cells with a composite electrolyte, while for the reference cell it was ∼23%.